GENETIC VARIABILITY INRAILY AND DABA ECORACES OF ANTHERAEA MYLITTA’ D. AND THEIRHYBIRDS - MAHOBIA, G.P.; YADAY, G.S.; RAO, K.V.S.; JAISHANKAR, C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
The present study presents the relevant information on phenotypic, genotypic variances, phenotypic and genotypic coefficient of variances, heritability and genetic advance on five genotypes of Antheraea mylitta D. viz. Raily, Daba, Raily x Daba (F1), F1 x Daba (BC1) and BC1, X Daba (BC2). Analysis of variance indicates significant differences among the five genotypes for all the traits under study (P<0.01, df 16). Phenotypic and genotypic variances in respect of mating %, fecundity, hatching %, effective rate of rearing, yield/dfl and absolute silk yield are higher whereas it was moderate in larval Weight, and low in larval period, spinning period, cocoon weight, shell weight and silk ratio, Higher heritability has been observed in all the traits except for larval period. High heritability (broad sense) with high genetic advance as percentage of mean in mating (%), ERR (%), shell weight (g), yield/dfl and absolute silk yield adjudicated additive gene effect, Moreover, fecundity, hatching %, spinning period, larval weight, cocoon weight and silk ratio have shown a high heritability with moderate genetic gain which is probably due to inter and intra allelic interactions, recurrent selection may be useful to improve these characters. The trait larval period presents moderate heritability with low genetic advance can be attributed to environmental influence.